(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Iodine deficiency disorder results in avoidable brain damage, cognitive impairment, and inhibited growth and development among children. The aim of this study was to ascertain pervasiveness of IDD in the Bhuj City of Kutch district of Gujarat by measuring urinary iodine excretion levels(UIE) and iodine intake from salt among school-going children. Material and methods: A cross-sectional investigation was conducted to evaluate iodine deficiency levels in 350 school children of both genders, 6-12 years of ages, from Bhuj Taluka, a subdivision of the Kachchh district. The evaluation involved estimating urinary iodine levels through the Sandell–Kolthoff reaction and determining the iodine levels in samples of cooking salt using Spot testing kit (STK). Results: With a median iodine levels in urine of 166.93 μg/L, there appears to be no biochemical evidence of iodine deficiency in the region. Approximately 98.57% of salt samples found iodine levels exceeding 15 ppm, while only about 1.42% had iodine levels below 15 ppm, indicating that household salt samples contain adequate iodine levels. Conclusions: The region’s median concentration of Iodine content found in urine 166.93 μg/L, suggesting the absence of biochemical iodine deficiency. Analysis of salt samples revealed that approximately 98.57% contained iodine levels exceeding 15 ppm, while only about 1.42% had iodine content below this threshold. This indicates that household salt samples possess adequate iodine levels, aligning with criteria for monitoring progress in eradicating iodine deficiency disorders as a public health concern.